Sistem Pakar Mendiagnosa Penyakit Radang Kulup Pada Pria Menggunakan Metode Case Based Reasoning - Nike Alpio Rizky; Relita Buaton; Siswan Syahputra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Balanitis is an inflammatory disease of the tip of the penis that commonly occurs in uncircumcised men as a result of poor hygiene and aeration or because of irritation by smegma and in many cases preputial dysfunction is a causal or contributing factor. Balanitis generally attacks uncircumcised men, characterized by the glans and foreskin becoming red and inflamed. In circumcised men who do not have a foreskin, these symptoms only affect the tip of the penis. This condition often occurs due to the fungus Candida albicans, the same organism that causes vaginal yeast infections in women. Balanitis (which is also referred to as balanoposthitis) can also be caused by various other fungal or bacterial infections, or can occur due to sensitivity reactions to common chemicals. Diabetes can increase the chance of developing balanitis, especially if blood sugar is not well controlled. Currently, people who experience illness or events that have not occurred before in the genitals will consult or diagnose their illness with a specialist in skin diseases to find out what disease they are experiencing. This requires time, energy and costs just to consult a doctor. The aim of conducting this research is that currently there is no system for diagnosing inflammation of the male foreskin. For this reason, the author will create an alternative application system that can diagnose diseases that occur in the male genitals more easily by asking questions about the symptoms or events experienced as factors in the disease and providing a percentage value regarding the severity of the disease experienced.